Implementación del software O4B en la gestión de control de proyectos en la Unidad Técnica de Gestión Vial de la Municipalidad de Osa - Valverde-Molina, Randall (Instituto Tecnológico de Costa Rica, 2017)
The implementation project of the Open for Business software "O4B" in the Municipality of Osa consists of applying this program in the control of road projects, using information from the projects that were being executed, facilitated by the Technical Unit of Road Management department. Once the work data is entered, the software starts up an effective and up-to-date project control system, which allows decisions to be made that promote the progress and satisfactory development of the projects. The main objective of the project is to improve the project control system that the Technical Road Management Unit has, moving from a manual revision and control model in electronic sheets to a computerized and automated digital model, in order to have a better control, regulation and update of the status of each road project that is being developed in the Municipality of Osa. This objective is intended to be developed with the help of the O4B software, a computational tool that has an integrated system of functions that allow improving processes and optimizing the control of resources and time of a project. This improvement is reflected in reports generated by the program, as well as bar graph statistics and other so-called S curves. The software was acquired after a previous inquiry that supported its purchase and implementation. Satisfactory results were obtained that support the use of the program, since it was demonstrated that it allows to have an integrated and updated control of all the variables inherent to a project control from the same software. Finally, it was elaborated in order to facilitate the use of the program; a simplified manual of the project module that will serve as a guide for the members of the road management department to develop a project from its initial stage.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Base de datos; Control; Proyectos; Software; Sistemas